PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS UNITY MATERI KOMUNIKASI PERKANTORAN PADA SISWA SMKN 22 JAKARTA - Mohammad Maulana; Roni Faslah; Eka Dewi Utari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Vocational education in Vocational High Schools (SMK) requires adequate practical facilities, especially in procedural and contextual Office Communication materials. The lack of interactive media utilization causes students to experience difficulties in internalizing professional communication operational standards. Therefore, this study aims to develop Unity-based interactive learning media in the form of a 2D Visual Novel simulation with a gamification approach, and to analyze its validity and practicality as a learning support media without measuring learning outcome effectiveness. This study uses the Research and Development (R&D) method through the Successive Approximation Model (SAM) approach, which consists of the preparation phase, iterative design phase, and iterative development phase. The unit of analysis in this study involved three expert validators (material, media, and instructional design) and a total of 45 11th-grade Office Administration students, gradually divided into one-to-one, small group, and field trials. Data collection techniques used Likert scale questionnaires, which were then analyzed using quantitative percentages. The validation results obtained the Highly Valid category from the material expert (94.44%), instructional design expert (80.00%), and media expert (76.67%). In the user formative evaluation stage, the small group trial obtained a score of 84.33% (Highly Practical) and the field trial obtained a score of 87.60% (Highly Practical). Students gave positive responses to the media's appeal because it presents branching dialogue and immediate feedback features that suit the Generation Z learning style. Research recommendations are addressed to schools to optimize Wi-Fi network facilities, to the department to integrate this media as practical variations, and to further researchers to conduct effectiveness tests, AI chatbot integration, Virtual Reality (VR) technology development, and collaborative multiplayer features.